Dipteran species in agricultural region of eastern Thessaloniki - THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ) Y.; GEORGOULAKIS (Ι. ΓΕΩΡΓΟΥΛΑΚΗΣ) I.; FOUNDA (Α. ΦΟΥΝΤΑ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
In an agricultural region of Thessaloniki province, fly traps were placed, which contained substances in order to attract flies with the purpose to trap and identify them. The substances were, pieces offish, meat and feta cheese, sugar and faeces of small ruminants. Fifteen different flies species were trapped, of which, thirteen are mentioned in the international bibliography, as parasites, such as, Musca domestica, Muscina sp, Fannia sp, Phormia regina, Lucilia (Phaenicia) sericata, Calliphora erythrocephala (vicina), Sarcophaga sp, Oestrus ovis, Gasterophillus sp, Stomoxys calcitrans, Haematobia (Shiphona) irritans, Chrysops sp and Hydrotaea (Ophyra) spp and two, as no parasites, such as Drosophilla melanogaster and Apis mellifera. From the trapped flies, Hydrotaea sp, Muscina sp, Fannia sp and Phormia regina, were identified for the first time in Greece. From the substances which were used in order to attract the flies, the fish was the one that all flies showed preference to, in the greater number, while the rest of the substances they chose descending order, was meat, sugar and feta cheese. Finally, only one fly was found in the excrement of small ruminants.